Semiotic Visual Analysis of Avant-Garde Fashion Designs in Ghana - Noble Nkrumah-Abraham; Genevieve Adjei-Appoh; Francis Kwasi Selormey Amenakpor (Fashion and Textiles Review)
Purpose: This study tends to appreciate the artistic and philosophical underpinnings and symbolic interpretation of some avant-garde design samples from the creative artist’s perspective. It also explores the familiarity, acceptance or otherwise of Ghanaians on Avant-garde artistry, practices, and culture based on the experiences of a Ghanaian avant-garde artist.